Epilepsy and Niemann Pick C disease - Munoz, Tatiana; Raiman, Julian A.J. (Journal of Pediatric Epilepsy, 2014)
Niemann-Pick disease type C (NPC) is an autosomal recessive, neurovisceral lipid storage disorder. Estimated to occur in one case every 120,000 live births. Approximately 95% of patients have mutations in the Niemann-Pick disease, type C1 (NPC1) gene and 5% in the Niemann-Pick disease, type C2 (NPC2) gene. It is a highly heterogeneous disease, characterized by visceral, neurological and psychiatric manifestations. Seizures are presented as unspecific feature in 33% of NPC patients, Seizures and cataplexy have been more often recorded among late infancy and juvenile-onset cases (37–57%) than early infancy (17%) and adolescent/adult onset (6–9%). Gelastic cataplexy represent the main differential diagnosis of seizures in a patient with NPC. In the current article, the nature of seizures in NPC, other non-epileptiform seizure like events, the frequency/impact on the disease course and their response to traditional and novel therapies as well as the outcome of a literature review is presented. Patients with NPC can experience any frequency and type of seizures, with reports suggesting they are an indicator of progression of disease. Refractory seizures have been reported in pediatric and adult populations, all of them associated with visceral, neurological and/or psychiatric symptoms. Electroencephalograms have been reported with non-specific background and interictal findings. Treatment with anticonvulsants and more recent disease specific treatments as Miglustat or hydroxypropyl-β-cyclodextrin have showed a variable response. Further studies are needed to elucidate specific features of NPC and epilepsy, as well as the impact of other developing specific therapies in seizure control.
Keywords: Niemann Pick C disease; seizures; epilepsy; cataplexy; neurological manifestations; treatment